(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The consequence of water logging on Beel Dakatia fisheries, the adaptability of people in terms of occupation with the new situation arisen and present livelihood conditions of fish and Prawn/ Galda (Macrobrachium rosenbergii) Gher farmers at Beel Dakatia in Dumuria, Phultala and Daulatpur thana under Khulna district were surveyed from April to September 2013. From the survey the community indicates that 21-40 age groups made maximum strength and majority of them were Muslims (58%). It was found that 16% of them can sign and the percentages of school going children were high (86%). In the study area, it was found that 62% of people lived with nuclear families and highest households were 5-7 people/family. Highest incomes of the people (44%) were 10,000 to 20,000 BDT. About 62% people lived in Katcha house and the construction materials were Golpata and Mud, 72% could be use electricity. Majority of the people (52%) % used others tube well water for drinking, 56% used closed semi pucca latrines. In any disease mostly preferred place were upazila hospital (52%). Thus to achieve better social structure, the Government and its development partner needs to re-orient their programmer and implementation an affirmative action for the fish and prawn gher farmers. It is also essential to improve the necessary training facilities with institutional and organizational supports, credit facilities and extension services for sustainable fish and prawn production and livelihoods of gher farmers. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22226 J. Environ. Sci. & Natural Resources, 7(2): 163-168 2014